Ovine Paratuberculosis: A Seroprevalence Study in Dairy Flocks Reared in the Marche Region, Italy - Attili Anna Rita; Ngu Ngwa Victor; Preziuso Silvia; Pacifici Luciana; Domesi Anastasia; Cuteri Vincenzo (Veterinary Medicine International)
In order to fulfil the seroprevalence gap on Mycobacterium avium subsp. paratuberculosis infection in ovine dairy farms of Marche region (central Italy), a stratified study was carried out on 2086 adult female sheep randomly chosen from 38 herds selected in Ancona and Macerata provinces. 73.7% flocks resulted infected by a commercial ELISA test (Pourquier, France), with a mean seroprevalence of 6.29% of sampled sheep in both provinces. A higher number of MAP seropositive ewes was recorded in the large herds' consistence than in the small and medium herds' consistence (𝑃=0.0269), and a greater percentage of infected sheep was obtained among female at early/late than in peak lactation stage (𝑃=0.0237). MAP infection was confirmed in 12.6% of infected farms by faecal culture. The true sheep-level seroprevalence was 15.1% ± 7.3%.